Otoritas dan Kekuasaan Kiai Menjaga Komitmen Sumber Daya Manusia Beda Agama di Pondok Pesantren Bali Bina Insani Tabanan Bali - Sudarsono, Sudarsono (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
The commitment of human resources in an organization is very important and influences the work relations. Organizational commitment cannot be separated from the term loyalty. Loyalty and commitment is a unity that has a confusing meaning. In simple terms, loyalty means how long employees work and obey the leadership's orders. This shows that maintaining commitment is an obligation for leaders. The commitment of human resources within the Bali BinaInsani Islamic Boarding School cannot be separated from the authority and power of the kiai as a leader. The kiai in the pesantren organization is the holder of full authority and power who can determine the path in maintaining the commitment of human resources of religious.